Analyzing Students' Needs in Learning Short Story Writing: An Exploratory Case Study in Indonesian Schools - Jasril Jasril; Asmawati Asmawati (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the learning needs of senior high school students in West Sumatra, Indonesia, regarding short story writing. Understanding these needs is essential to develop effective instructional strategies that enhance students’ writing skills. A qualitative research design employing a descriptive analysis method was used. Data were collected through an exploratory case study involving 295 students and 15 teachers from four senior high schools. Instruments included short story writing tests, student questionnaires, and interviews with both students and teachers. The collected data were analyzed using content analysis techniques. Findings indicate that students benefit from a problem-based flipped classroom model, where they study materials at home and complete tasks in class. They also require a problem-based learning approach that emphasizes autonomy, motivation, creativity, logical reasoning, and experiential learning. Preferred learning media are digital, engaging, and flexible—accessible from home and adaptable to individual pacing. In terms of assessment, students favor ongoing, collaborative evaluations that align with the learning process. They also value assessments that directly support the development of their writing skills through constructive feedback and skill-targeted assignments. The results suggest that integrating digital tools and active learning models can better support students’ engagement and progress in short story writing. Instructional designs should reflect students' preferences for autonomy, creativity, and continuous feedback.